We have to solve: log(3x + 5) (9x*x + 8*x +2) > 2

log(3x + 5) (9x*x + 8*x +2) > 2

=> 9x*x + 8*x +2 > (3x + 5)^2

=> 9x^2 + 8x + 2 > 9x^2 + 30x + 25

=> 8x - 30x > 25 - 2

=> -22x > 23

=> x < -23/22

But the base of the logarithm has to be greater than 0

=> 3x + 5 > 0

=> x > -5/3

**The solution of the inequality is -5/3 < x <
-23/22**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.